Estrogen-induced disruption of intracellular iron metabolism leads to oxidative stress, membrane damage, and cell cycle arrest in MCF-7 cells - Khuloud Bajbouj; Jasmin Shafarin; Maher Y Abdalla; Iman M Ahmad; Mawieh Hamad (Tumor Biology)
It is well established that several forms of cancer associate with significant iron overload. Recent studies have suggested that estrogen (E2) disrupts intracellular iron homeostasis by reducing hepcidin synthesis and maintaining ferroportin integrity. Here, the ability of E2 to alter intracellular iron status and cell growth potential was investigated in MCF-7 cells treated with increasing concentrations of E2. Treated cells were assessed for intracellular iron status, the expression of key proteins involved in iron metabolism, oxidative stress, cell survival, growth, and apoptosis. E2 treatment resulted in a significant reduction in hepcidin expression and a significant increase in hypoxia-inducible factor 1 alpha, ferroportin, transferrin receptor, and ferritin expression; a transient decrease in labile iron pool; and a significant increase in total intracellular iron content mainly at 20 nM/48 h E2 dose. Treated cells also showed increased total glutathione and oxidized glutathione levels, increased superoxide dismutase activity, and increased hemoxygenase 1 expression. Treatment with E2 at 20 nM for 48 h resulted in a significant reduction in cell growth (0.35/1 migration rate) and decreased cell survival (<80%) as compared with controls. Survivin expression significantly increased at 24 h post treatment with 5, 10, or 20 nM; however, that of γ-H2AX increased only after survivin levels dropped and only at the 20 nM E2 dose. Minimal upregulation and splitting of caspase 9 was only evident in cells treated with 20 nM E2; no changes in caspase 3 expression were evident. Although Annexin V staining studies showed that E2 treatment did not induce apoptosis, scanning electron microscopy studies showed marked membrane blebbing at 20 nM/48 h of E2. These findings suggest that estrogen treatment disrupts intracellular iron metabolism and precipitates adverse effects concerning cell viability, membrane integrity, and growth potential.